Pelatihan Reflective Thinking untuk Meningkatkan Kesadaran Orientasi Masa Depan Siswa SMAN 11 Pangkaje’ne Sulawesi Selatan - Saleh, Umniyah; Jamil, Rizky Amalia; Usman, Yassir Arafat; Arfah, Triani (Devotion : Jurnal Pengabdian Psikologi, 2024)
Adolescents are the next generation of the nation who will contribute greatly to the development of Indonesia’s human resources. The adolescent phase is an important stage to start forming a clear self-identity including in terms of future planning. However, adolescents often experience confusion regarding their future orientation, making it difficult to set goals and strategies to achieve the future. Although most of them have aspirations, it is less based on the ability to recognize themselves related to their strengths and weaknesses. According to the literature review, the reflective thinking method applied through reflection of experience is an important learning model. With this method, individuals can better recognize their potential based on the meaning of their past experiences. This training was conducted for two days on 24 - 25 May 2023 at SMA Negeri 11 Pangkaje'ne, with a total of 31 participants who were students of class XI. The results of this training show that the ability to think reflectively in interpreting experiences will help adolescents recognize their strengths and weaknesses, as well as their interests and talents. This can be a reference for them in setting future goals. A clear future direction can lead adolescents to set specific steps and strategies to achieve their goals. This will increase the chances for adolescents to get a decent job and have a career that suits their potential in the future.